The Jesuit Order as a Synagogue of Jews Jesuits of Jewish Ancestry and Purity-of-Blood Laws in the Early Society of Jesus - Maryks, Robert Aleksander (Brill, 2009)
In The Jesuit Order as a Synagogue of Jews the author explains how Christians with Jewish ancestry went within less than forty years from having a leading role in the foundation and development of the Society of Jesus to being prohibited from membership in it.